APPLICATION OF NANOPARTICLES FOR THE CONTROL OF Colletotrichum gloeosporioides CAUSING ANTHRACNOSE DISEASE OF CHILI (Capsicum frutescens L.) - Huy Gioi, Dong; Thi Men, Nguyen; Viet Cuong, Ha; Thi Thu Huong, Bui (Journal of Forestry Science and Technology, 2022)
Chili (Capsicum annum L.) was one of the most important seasoning constituents of the cuisines of many countries in the world and it was ranked the fourth major crop cultivated globally. However, Anthracnose disease caused by Colletotrichum gloeosporioides has affected chili production worldwide, especially in tropical and subtropical regions. It is necessary to have greatly effective disease management. Therefore, this study had examined the antifungal effect of some nano solutions on C. gloeosporioides in both in vitro and in vivo conditions. The results clearly demonstrated that silver nano, copper nano, and silver-copper nano solutions had inhibited the spore germination and the growth of C. gloeosporioides. Inhibitory effects were 100% mycelial diameter at the solutions with concentrations of 125 ppm silver nano or 75 ppm copper nano or 50 ppm mixed silver-copper nano. The medium with the concentration of 75 ppm silver nano or 25 ppm copper nano or 12.5 ppm silver-copper nano solution completely inhibited spore germination of C. gloeosporioides. In vivo experiment, the silver-copper solutions with a concentration of 50 ppm could control the growth of C. gloeosporioides in chili fruits the findings were that there were only 13.3% disease fruits, and the inhibition efficiency was 86.7%.